Assessing the performance of CFRP strengthening on masonry walls using experimental modal analysis. (15th August 2019) - Bernat-Masó, Ernest; Gil, Lluís
Graphical abstract: Highlights: Modal analysis detects frequency vibration changes due to CFRP strengthening. Bending vibration modes are the most sensitive ones. Low frequency vibration modes are the most reliable ones. Analytically predicted frequency of vibration of strengthened walls meets experimental results. Abstract: Strengthening masonry structures using FRP laminates has been widely studied from a resistance point of view. However, there is a need of a non-destructive technique to validate strengthening interventions. In this paper, experimental modal analysis is proposed as a technique to assess practitioners' works. Fifteen brick masonry walls were built and strengthened with five different patterns of carbon-FRP laminates. Experimental modal analysis was performed before and after strengthening interventions. Different vibration modes were compared to select the more sensitive one depending on the strengthening configuration. The change in the vibration frequency was analysed and correlated with cross-section stiffness modification. The obtained results showed changes up to 30% on the vibration frequencies due to strengthening installation. On the overall, the proposed experimental methodology is supported by theoretical analytical calculations with an error under 5% in most of the cases.